Beyond Bogotá : diary of a drug war journalist in Colombia - Leech, Garry M. (Beacon Press, 2009)
"Beyond Bogota is framed around the eleven hours that Leech was held captive by the FARC, Colombia's largest leftist guerrilla group, in August of 2006. He recalls nearly thirty years of travel and work in Latin America while weaving in a historical context of the region and on-the-ground reporting with each passing hour of his detention." "Drawing on unprecedented access to soldiers, guerrillas, paramilitaries, and peasants in conflict zones and cocaine-producing areas, Leech's documentary memoir is an epic tale of a journalist's search for meaning in the midst of violence and poverty, as well as a humanizing firsthand account that supplies fresh insights into U.S. foreign policy, the role of the media, and the plight of everyday Colombians caught in the midst of a brutal war."--Jacket